PENGARUH KEADILAN SISTEM PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Kajian Empiris di KPP Madya Kota Pekanbaru) - Dini Suhartini; Amries Rusli Tanjung; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the impact of tax compliance variable consist of justice system of taxation, tax penalties, and motivation as an intervening variable. Research was conducted using a questionnere survey on corporate taxpayers in KPP Madya Pekanbaru. It uses incidental sampling techniques and selected 100 sample. Method used in this research is quantitative method, partial analysis and simultaneous (analysis partial least square). The result shows that none of tax penalties and motivation influence on tax compliance and justice systemof taxation influence on motivation. But the justice system of taxation does not effect the tax compliance and tax penalties don’t effect the motivation.Keywords: Tax Compliance, justice sistem of taxation, tax penalties, and motivation.